Investigating the complex relationships between leadership, psychological safety, intrinsic motivation, and nurses’ voice behavior in public hospitals using PLS-SEM - Thuraisyah Jaaffar; Naresh Kumar Samy (Belitung Raya Foundation, Indonesia, 2023)
Background: Voice behavior among nurses in public hospitals lacks profound disclosure despite knowing its imperatives. This situation needs to be continuously studied, and the best practices discovered, disclosed, and implemented in hospitals that are serious in curbing unprofessional conduct while advancing healthcare requirements for the benefit of humanity. Objective: This empirical research investigated the significant implications of psychological safety and intrinsic motivation in the mostly uncultivated link concerning the empowering leadership style and leader-member exchange (LMX) constructs and the practice of voice behavior among nurses in the selected Malaysian public hospitals. Methods: Primary data of the study were from nurses employed in the selected large public hospitals within the Klang Valley, also known as the Greater Kuala Lumpur of Malaysia. A total of 366 complete and valid responses were collected with the help of head nurses via a self-administered survey in February 2020. The SmartPLS 4 for Windows software generated the standard partial least squares structural equation modeling (PLS-SEM) to estimate associations between research variables and evaluate the model’s strength in explaining the proposed constructs. Results: This research disproved the indirect effects of psychological safety on the connection explorations between empowering leadership-voice behavior (β = 0.015, t-value = 0.300, 95% CI [-0.090, 0.110]) and LMX-voice behavior (β = 0.002, t-value = 0.285, 95% CI [-0.014,0.020]). Intrinsic motivation partially mediates the link between empowering leadership-voice behavior (β = 0.214, t-value = 7.116, 95% CI [0.160, 0.279]) and LMX-voice behavior (β = 0.114, t-value = 4.669, 95% CI [0.071, 0.168]) of the nurses. Conclusion: Patients, non-governmental organizations, volunteers, nurses, and other hospital staff are vested in how voice behavior signifies in the healthcare context. Essential factors for nurses to become more outspoken are discovered in this study, providing nurse managers and other leaders with numerous recommendations for encouraging vocal behavior and bolstering psychological safety and intrinsic motivation. More competent nurses will improve workplace culture, deliver superior healthcare services, and manage publicly financed hospitals with an overall sense of trust, but only after a substantial effort to execute reforms.